Analisis Realisasi Penerimaan Negara Bukan Pajak Badan Layanan Umum Politeknik Keuangan Negara STAN Tahun Anggaran 2022-2024 - Satria Adhitama; Bayu Auguste Bartholdi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the realization of Non-Tax State Revenue (PNBP) at the Public Service Agency (BLU) of the State Finance Polytechnic STAN (PKN STAN) during the 2022–2024 fiscal years. The research employs a descriptive qualitative approach utilizing documentation data and PNBP realization reports as the primary sources of analysis. The findings indicate that PKN STAN's PNBP realization experienced significant dynamics across various revenue categories. Revenue from educational services showed a substantial increase in 2024, exceeding the established targets, driven by the expansion of non-regular education programs, educational collaborations with government institutions and regional governments, as well as the implementation of the talent development program. Foreign grant revenues also increased significantly, particularly through cooperation with the Asian Development Bank (ADB). However, several revenue categories, such as institutional partnerships and individual cooperation revenues, experienced fluctuations and declines during certain periods. The study reveals that PNBP optimization is influenced by internal factors, including service innovation, educational program development, asset utilization, and service digitalization, as well as external factors such as post-pandemic economic recovery, regulatory support, and the expansion of inter-institutional cooperation. This research provides recommendations for PKN STAN and other educational BLUs to strengthen revenue diversification strategies, improve service quality, and optimize the use of technology and strategic partnerships to enhance sustainable PNBP performance.